Gendered Questions, Gendered Outcomes: Exploring Bias in Startup Funding Pitches and its Impact on Female Entrepreneurs - Mader,Katja Anna; Olsson,Lovisa (2025)
Despite increased attention to gender equality in entrepreneurship, women remain significantly underrepresented in entrepreneurship and receive a disproportionately small share of funding. One underexplored factor contributing to this disparity is gendered questioning during investor pitches. The study aimed to explore how gendered questioning shapes confidence and self-perception, and to investigate further how industry-specific factors interplay with these dynamics. This study draws on theories of Regulatory Focus, Role Congruity, and Entrepreneurial Identity. A qualitative research design was employed, combining semi-structured interviews with female entrepreneurs and complementary observational data from pitch interactions in Dragons’ Den to generate in-depth insights into gendered dynamics in startup funding. The study finds that female entrepreneurs are disproportionately asked prevention-focused questions during startup pitches, which fosters internalized doubt, reduces confidence, and reinforces gendered expectations of risk aversion. Moreover, industry context moderates these experiences: women in female-dominated sectors face devaluation, while those in male-dominated fields encounter heightened scrutiny and credibility challenges. The study shows that confidence and legitimacy are shaped through gendered pitch interactions, manifesting that confidence and legitimacy are not fixed traits but co-constructed through investor-founder dynamics. It extends existing theory and offers practical insights for reducing bias in startup funding.
Keywords: Female Entrepreneurship; Gendered Questioning; Funding Disparity; Gender Stereotypes; Investor Bias; Entrepreneurial Confidence; Dragons’ Den